Use of Tumor Necrosis Factor-α Antagonists Is Associated With Attenuated IgG Antibody Response Against SARS-CoV-2 in Vaccinated Patients With Inflammatory Bowel Disease - Otten, Antonius T.; Bourgonje, Arno R.; Horinga, Petra P.; van der Meulen, Hedwig H.; Festen, Eleonora A. M.; van Dullemen, Hendrik M.; Weersma, Rinse K.; van Leer-Buter, Coretta C.; Dijkstra, Gerard; Visschedijk, Marijn C. (Frontiers in Immunology, 2022)
Introduction: Patients with Inflammatory Bowel Disease (IBD) frequently receive immunomodulating treatment, which may render them at increased risk of an attenuated immune response upon vaccination. In this study, we assessed the effects of different types of commonly prescribed immunosuppressive medications on the serological response after vaccination against SARS-CoV-2 in patients with IBD. Methods: In this prospective observational cohort study, IgG antibody titers against SARS-CoV-2 were measured 2-10 weeks after completion of standard vaccination regimens in patients with IBD. Clinical characteristics, previous history of SARS-CoV-2 infection, type of vaccine (mRNA- or vector-based) and medication use were recorded at the time of sampling. Subsequently, a chemiluminescent microparticle immunoassay was used for the quantitative determination of IgG antibodies against the receptor-binding domain (RBD) of the S1 subunit of the spike protein of SARS-CoV-2. Results: Three hundred and twelve (312) patients with IBD were included (172 Crohn’s disease [CD] and 140 ulcerative colitis [UC]). Seroconversion (defined as titer of >50 AU/ml) was achieved in 98.3% of patients. Antibody concentrations were significantly lower in patients treated with TNF-α-antagonists vs. non-users of TNF-α-antagonists (geometric mean [95% confidence interval]: 2204 [1655-2935] vs. 5002 [4089-6116] AU/ml, P<0.001). In multivariable models, use of TNF-α-antagonists (P<0.001), vector vaccines (P<0.001), age (>50 years) (P<0.01) and CD (P<0.05) were independently associated with lower anti-SARS-CoV-2 antibody titers. In patients who received mRNA vaccines, users of thiopurines (either prescribed as monotherapy or in combination with biologicals) demonstrated significantly lower antibody titers compared to those who were thiopurine non-users (P<0.05). Conclusion: Despite reassuring findings that most patients with IBD have detectable antibodies after anti-SARS-CoV-2 vaccination, TNF-α-antagonists were found to be strongly associated with an attenuated IgG antibody response after vaccination against SARS-CoV-2, independent of vaccine type, the time elapsed after vaccination and blood sampling, prior SARS-CoV-2 infection and patient age. Patients treated with thiopurines and receiving mRNA-based vaccines demonstrated lower anti-SARS-CoV-2 antibody titers compared with non-users.